1998
DOI: 10.1007/s004150050180
|View full text |Cite
|
Sign up to set email alerts
|

Transcortical sensory aphasia following left frontal infarction

Abstract: Two right-handed patients who exhibited language disability after left frontal infarction are described. The patients spoke fluently and exhibited excellent repetition ability from the onset of infarction without exhibiting any oral apraxia, but had deficits in auditory comprehension, naming, reading and writing. In both patients, brain magnetic resonance imaging (MRI) revealed infarction in the left inferior frontal gyrus, the middle frontal gyrus and the anterior part of the lower precentral gyrus. Single ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
(40 reference statements)
0
18
0
2
Order By: Relevance
“…However, there may be considerable variation among and within subjects in both the gross structure and the cytoarchitecture of the IFG, and the cytoarchitectonic borders do not consistently coincide with sulcal boundaries (Bailey and Bonin, 1951;Ebeling et al, 1989;Amunts et al, 1999;Tomaiuolo et al, 1999;Damasio, 2005). Since Broca's original description of the effects of lesions of this area on speaking ability (1861; see translation by von Bonin, 1950), evidence for the IFG as a structure critical for speech and language function has come from many studies using a variety of experimental approaches including lesion/behavior (Mohr et al, 1978;Damasio and Geschwind, 1984), electrical stimulation functional mapping (Penfield and Roberts, 1959;Ojemann, 1979;Lesser et al, 1984;Ojemann et al, 1989), functional magnetic resonance imaging (fMRI; Wildgruber et al, 1996;Paulesu et al, 1997;Lazar et al, 2000), magnetoencephalography (MEG; Sasaki et al, 1995;Dhond et al, 2001), positron emission tomography (PET; Klein et al, 1997;Bookheimer et al, 2000;Caplan et al, 2000), and singlephoton emission computed tomography (SPECT; Otsuki et al, 1998). These studies suggest that the IFG region is involved in numerous language-specific tasks including phonologic, semantic, and sentence-and discourse-level processing, as well as detection of the emotional content of speech (Gernsbacher and Kaschak, 2003;Martin, 2003).…”
mentioning
confidence: 98%
“…However, there may be considerable variation among and within subjects in both the gross structure and the cytoarchitecture of the IFG, and the cytoarchitectonic borders do not consistently coincide with sulcal boundaries (Bailey and Bonin, 1951;Ebeling et al, 1989;Amunts et al, 1999;Tomaiuolo et al, 1999;Damasio, 2005). Since Broca's original description of the effects of lesions of this area on speaking ability (1861; see translation by von Bonin, 1950), evidence for the IFG as a structure critical for speech and language function has come from many studies using a variety of experimental approaches including lesion/behavior (Mohr et al, 1978;Damasio and Geschwind, 1984), electrical stimulation functional mapping (Penfield and Roberts, 1959;Ojemann, 1979;Lesser et al, 1984;Ojemann et al, 1989), functional magnetic resonance imaging (fMRI; Wildgruber et al, 1996;Paulesu et al, 1997;Lazar et al, 2000), magnetoencephalography (MEG; Sasaki et al, 1995;Dhond et al, 2001), positron emission tomography (PET; Klein et al, 1997;Bookheimer et al, 2000;Caplan et al, 2000), and singlephoton emission computed tomography (SPECT; Otsuki et al, 1998). These studies suggest that the IFG region is involved in numerous language-specific tasks including phonologic, semantic, and sentence-and discourse-level processing, as well as detection of the emotional content of speech (Gernsbacher and Kaschak, 2003;Martin, 2003).…”
mentioning
confidence: 98%
“…The preserved speech fluency in our TSA1 and TSA2 patients may be explained by the relatively preserved precentral gyrus and superior frontal lobe as compared to TSM patients (Fig. 1), that were reported to be responsible for spontaneous speech production [2,3,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, patients with left frontal lobe lesions presenting with TSA have been reported [2,3,4,5,6], but the underlying mechanisms remain unclear. We studied 2 patients with TSA due to left frontal lobe lesions using multimodal MRIs to clarify the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Nonfluent aphasias such as Broca's area and transcortical motor type aphasia are known to be caused by lesions of the anterior language area in the left frontal lobe [1], but few reports have described fluent aphasia caused by lesions in the frontal lobe [2][3][4]. We report a case of transcortical sensory aphasia characterized by fluent speech, poor comprehension and preserved repetition following infarction in the left frontal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature disclosed that 35% of isolated DCVT cases were fatal [1,2,[4][5][6][7][8][9]. A prospective study of 59 patients also suggested that involvement of the straight sinus and the deep venous system may be associated with poor outcome [3].…”
mentioning
confidence: 99%